FINANCING TO DEPOSIT RATIO (FDR) PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2020 - Niken Ayu Anggi Pratiwi (2022)
Sharia bank is a bank that conducts its business activities based on sharia principles and based on its type consists of Sharia Commercial Banks and Sharia People's Financing Banks. Islamic Commercial Banks are Islamic banks that offer payment transaction services. In other words, Islamic banks act as financial institutions, collecting funds from the public and redistributing them to the public. The liquidity ratio is used to analyze the bank's ability to fulfill its obligations. A bank is declared liquid if it is able to pay off all of its debts, can repay all customer deposits, and pay off all loan applications submitted without any suspension. Financing to Deposit Ratio (FDR) is an indicator that measures the level of bank liquidity in making repayments for withdrawals of third party funds by dividing the amount of financing as a source of liquidity.